Pengaruh Pemberian Rumput Lapangan dan Daun Lamtoro Gung Terhadap Pertambahan Bobot Badan dan Bobot Badan Akhir Kelinci Lokal Jantan (Erictolagus cuniculus) - Kastalani Kastalani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2013)
This study aims to determine the effect of field grass and leaf of lamtoro gung on body weight gain and final body weight of local male hare. This experiment using completely randomized device (CRD), with five treatment and four replications. The result showed that the use of field grass and leaf of lamtoro gung have significant effect on body weight gain and final body weight of local male hare.